Implementasi Media Podcast Mini Bahasa Arab Berbasis Project-Based Learning Dalam Pembelajaran Maharah Kalam Siswa MAN - Ahmad Tarikul Majid; Wafirotul Laila; Asep Sunarko (IAIN Bone, 2026)
Arabic speaking (maharah kalam) instruction in Madrasah Aliyah continues to face several challenges, including students' low self-confidence, limited opportunities for speaking practice, and the use of instructional media that has not yet effectively promoted active communication. This study aimed to describe the implementation of mini podcast media based on Project-Based Learning (PjBL) in Arabic speaking instruction and to explore its contribution to the development of students' speaking competence and twenty-first-century skills. This study employed a qualitative approach using a case study design conducted at a public Madrasah Aliyah in Wonosobo Regency, Indonesia. The research participants consisted of one Arabic language teacher and several eleventh-grade students selected purposively because they were directly involved in learning activities using PjBL-based mini podcast media. Data were collected through classroom observations, semi-structured interviews, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The findings revealed that the implementation of PjBL-based mini podcast media was carried out through five stages: project orientation, script writing, audio recording, audio editing, and project presentation. The findings also indicated that the use of mini podcast media provided a more active and contextual learning experience and was perceived by both the teacher and students to support the development of vocabulary mastery, grammatical accuracy, pronunciation, speaking fluency, and self-confidence. Furthermore, project-based learning facilitated the development of communication, collaboration, creativity, critical thinking, and digital literacy skills. The study also identified several challenges, including differences in students' Arabic language proficiency, limited instructional time, and technical issues during the podcast production process, which were addressed through teacher guidance and effective use of available technology. Therefore, PjBL-based mini podcast media can serve as an innovative and contextual alternative for supporting Arabic speaking instruction in Madrasah Aliyah